2022
DOI: 10.3390/ijms23031794
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Malus baccata MYB Transcription Factor Gene MbMYB4 Increases Cold and Drought Tolerance in Arabidopsis thaliana

Abstract: In the natural environment, plants often face unfavorable factors such as drought, cold, and freezing, which affect their growth and yield. The MYB (v-myb avian myeloblastosis viral oncogene homolog) transcription factor family is widely involved in plant responses to biotic and abiotic stresses. In this study, Malus baccata (L.) Borkh was used as the research material, and a gene MbMYB4 of the MYB family was cloned from it. The open reading frame (ORF) of MbMYB4 was found to be 762 bp, encoding 253 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In the whole life cycle of plants, they are often affected by various environmental factors that are not conducive to growth, such as saline alkali conditions, drought, high temperature, iron deficiency, cold and lack of nutrition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In order to survive under various adverse conditions and carry out normal life activities, plants will produce different adaptation mechanisms [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the whole life cycle of plants, they are often affected by various environmental factors that are not conducive to growth, such as saline alkali conditions, drought, high temperature, iron deficiency, cold and lack of nutrition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In order to survive under various adverse conditions and carry out normal life activities, plants will produce different adaptation mechanisms [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor is mainly responsible for sensing and transducing early responses to salt stress in plants, such as DREB (dehydration responsive element binding factors), bZIP (basic leucine zipper), MYB (v-myb avian myeloblastosis viral oncogene homolog), and so forth. As one of the most important transcription factor families in plants, MYB transcription factors are widely involved in abiotic stress resistance, such as salt stress, drought stress and so on ( Yu et al, 2017 ; Yao et al, 2022 ). Some studies have confirmed that overexpression of MYB gene can improve the salt tolerance of transgenic plants ( Shen et al, 2018 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the other species, GaMYB85 of Gossypium aridum , homolog with AtMYB85 from S8, reportedly play an important role in the drought tolerance of plants [ 34 ]. R2R3-MYB gene MdoMYB121 from Malus domestica , MbMYB4 from M. baccata, and PlMYB108 (S20) from Paeonia lactiflflora were involved in increasing drought tolerance [ 35 , 36 , 37 ]. Notably, these functional genes were detected in S8 and S20.…”
Section: Discussionmentioning
confidence: 99%